2016
DOI: 10.1002/app.44415
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of hollow glass microsphere with different coupling agents for potential applications in phenolic syntactic foams

Abstract: Modified hollow glass microsphere (HGM) particles have been prepared by surface treatment. Coupling agents such as γ‐aminopropyltriethoxysilane (APTES), di(dioctylpyrophosphato) ethylene titanate (NDZ‐311), and glutaraldehyde (GA) were used as modifiers to improve the hydrophobicity of HGM. Compared with pristine HGM, the modified HGM, especially the particles coupled with APTES‐GA, show better properties on flexural strength, fracture toughness, and dynamic mechanical properties of phenolic syntactic foams. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 40 publications
1
29
1
Order By: Relevance
“…Due to their outstanding integrated performances, including high thermal and mechanical properties and good radiation and corrosion resistance, high‐performance thermosetting resins (HPTRs) have important applications in many cutting‐edge industrial fields such as aerospace, electronic information, electrical insulation, and new energy . However, in recent years, increasing requirements for good flame retardancy and suppression of toxic volatiles have been put on HPTRs …”
Section: Introductionmentioning
confidence: 99%
“…Due to their outstanding integrated performances, including high thermal and mechanical properties and good radiation and corrosion resistance, high‐performance thermosetting resins (HPTRs) have important applications in many cutting‐edge industrial fields such as aerospace, electronic information, electrical insulation, and new energy . However, in recent years, increasing requirements for good flame retardancy and suppression of toxic volatiles have been put on HPTRs …”
Section: Introductionmentioning
confidence: 99%
“…The ammonium bicarbonate solid is used as foaming agent. 9 In this experiment, the total quantity values of epoxy resin, glass microsphere and curing agent are 60.0 g, 5.0 g and 10.0 g, respectively. The epoxy resin and curing agent are mixed by magnetic stirrer (DF 101 S, 1000 r/min), and the samples of epoxy-glass microsphere composite are fabricated according to the following steps: (i) Pre-treating: The surface of the glass microsphere powder is pre-treated with the KH-550 coupling agent, the weight of which is 5 wt% of the glass microsphere used in this step, i.e.…”
Section: Methodsmentioning
confidence: 92%
“…Additionally, air trapped by this viscous mixture cannot be eliminated in the degassing process, whereas after the resin curing, the air becomes matrix pores (sometimes up to 11 vol.%). Some previous studies 4,2225 have shown that matrix pores are the defects, which affect the properties of composites, especially its compressive strength.…”
Section: Introductionmentioning
confidence: 99%